2023
DOI: 10.3389/fphar.2022.1059360
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of tanshinone in regulating autophagy for medicinal research

Abstract: Initially described as an ancient and highly conserved catabolic biofunction, autophagy plays a significant role in disease pathogenesis and progression. As the bioactive ingredient of Salvia miltiorrhiza, tanshinone has recently shown profound effects in alleviating and treating various diseases by regulating autophagy. However, compared to the remarkable achievements in the known pharmacological effects of this traditional Chinese medicine, there is a lack of a concise and comprehensive review deciphering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Some EZH2 inhibitors, like DS-3201b, are in phase 2 clinical trials for solid tumors ( Izutsu et al, 2023 ). Traditional Chinese medicines have demonstrated unique advantages in managing CVDs, and screening for EZH2 inhibitor among them is a feasible strategy ( Li et al, 2020 ; Zhao et al, 2020 ; Wang et al, 2021 ; Li et al, 2022 ; Wu et al, 2022 ; Hou et al, 2024 ; Qi et al, 2024 ; Wang et al, 2024 ; Zhao et al, 2024 ). In personalized medicine, EZH2 can serve as a breakthrough point for individualized CVD treatment, enabling accurate diagnosis and treatment based on related biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Some EZH2 inhibitors, like DS-3201b, are in phase 2 clinical trials for solid tumors ( Izutsu et al, 2023 ). Traditional Chinese medicines have demonstrated unique advantages in managing CVDs, and screening for EZH2 inhibitor among them is a feasible strategy ( Li et al, 2020 ; Zhao et al, 2020 ; Wang et al, 2021 ; Li et al, 2022 ; Wu et al, 2022 ; Hou et al, 2024 ; Qi et al, 2024 ; Wang et al, 2024 ; Zhao et al, 2024 ). In personalized medicine, EZH2 can serve as a breakthrough point for individualized CVD treatment, enabling accurate diagnosis and treatment based on related biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alp activates the apoptosis pathway by inhibiting the expression of the anti-apoptotic protein BCL2 [ 59 ]. Furthermore, the expression differences in autophagy-related proteins, ATG3 [ 60 ] and LC3 [ 61 ], indicated that mitochondrial autophagy function is impaired. In summary, mitochondrial dysfunction caused by repeated administration of Alp reflected the damage to the mitochondrial respiratory chain, mitochondrial dynamics, and mitochondrial autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alp activates the apoptosis pathway by inhibiting the expression of the anti-apoptotic protein BCL2 [59]. Furthermore, the expression differences in autophagy-related proteins, ATG3 [60] and LC3 [61],…”
Section: Discussionmentioning
confidence: 99%
“…P62 and LC3 serve as markers reflecting autophagic activity. In conditions of low autophagy or inhibition, P62 accumulates in the cytoplasm, while the LC3-II/I ratio indicates the level of autophagy 107 - 110 . Studies have shown that autophagy can exert dual effects on tumor occurrence and progression 111 , 112 .…”
Section: Functional Roles and Mechanisms Of Circrna In Hnsccmentioning
confidence: 99%